2021
DOI: 10.1016/j.sdentj.2020.12.007
|View full text |Cite
|
Sign up to set email alerts
|

LuxS quorum sensing system and biofilm formation of oral microflora: A short review article

Abstract: The LuxS quorum sensing system is considered as the main system that most of the oral bacteria use to communicate in order to create biofilms. Here we identified 11 of the most important biofilm formers that utilize the LuxS system and presented current and recent information regarding this system. Though different bacterial species are able to communicate thorough the LuxS system, it was also found that cross kingdom communication can occur between bacteria and fungi and bacteria and epithelial cells. Immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…IS3 family transposase and elongation factor TU were significantly more highly expressed in SS-128 than in the luxS -mutant strain, whereas the DNA-binding protein II and ornithine carbamoyltransferase were concentrated in the luxS -mutant strain. Furthermore, it was reported that the expression of DNA-binding protein was related to the AI-2/LuxS QS system ( Niazy, 2021 ). The 6-phospho-beta-glucosidase was upregulated in SS-128, which participates in the energy metabolism ( Acin-Albiac et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…IS3 family transposase and elongation factor TU were significantly more highly expressed in SS-128 than in the luxS -mutant strain, whereas the DNA-binding protein II and ornithine carbamoyltransferase were concentrated in the luxS -mutant strain. Furthermore, it was reported that the expression of DNA-binding protein was related to the AI-2/LuxS QS system ( Niazy, 2021 ). The 6-phospho-beta-glucosidase was upregulated in SS-128, which participates in the energy metabolism ( Acin-Albiac et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…AI-2 is a chemical compound (furanosyl borate) formed from its precursor DPD (4,5-dihydroxy-2,3-pentanedione) [ 61 , 62 ]. AI-2 is acclaimed as a ‘universal autoinducer’ as it facilitates interspecies communication [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although luxS expression in S. mutans is associated with biofilm formation and biofilm structure maintenance, its roles in regulating the factors critical to biofilm formation are unresolved [ 36 ]. However, it has been found that the LuxS quorum sensing system is considered the main system that most of oral bacteria use to communicate within biofilm [ 47 ]. The most common and widespread quorum sensing signal among bacteria is autoinducer-2, which is a signaling molecule induced by LuxS that regulates the expression of numerous genes, including gtfB/C genes [ 48 ].…”
Section: Discussionmentioning
confidence: 99%